2012
DOI: 10.2337/dc11-1485
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Replacing Sucrose by Isomaltulose in Subjects With Type 2 Diabetes

Abstract: OBJECTIVETo test the hypothesis that replacement of sucrose with isomaltulose in sweet foods and beverages improves metabolic control in patients with type 2 diabetes.RESEARCH DESIGN AND METHODSOne hundred ten patients with type 2 diabetes were randomized to receive sweet foods containing either 50 g/day isomaltulose or sucrose for 12 weeks as part of their habitual diet under free-living conditions. HbA1c at 12 weeks was the primary outcome parameter.RESULTSIn the final analysis comprising 101 patients, isoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…However, the effect of this carbohydrate in subjects with T2DM has been barely explored. Brunner et al did not observe significant changes in glucose metabolism after intake of 50 g/d of isomaltulose during 12 weeks although they did denote a significant decrease in triglycerides compared with those participants consuming 50 g/d of sucrose [30]. Another research study demonstrated that the ingestion of 1 g/kg-isomaltulose attenuated postprandial hyperglycemia by reducing oral glucose appearance and inhibiting endogenous glucose production, in comparison with the intake of rapidly absorbed sucrose in patients with T2DM [31].…”
Section: Discussionmentioning
confidence: 95%
“…However, the effect of this carbohydrate in subjects with T2DM has been barely explored. Brunner et al did not observe significant changes in glucose metabolism after intake of 50 g/d of isomaltulose during 12 weeks although they did denote a significant decrease in triglycerides compared with those participants consuming 50 g/d of sucrose [30]. Another research study demonstrated that the ingestion of 1 g/kg-isomaltulose attenuated postprandial hyperglycemia by reducing oral glucose appearance and inhibiting endogenous glucose production, in comparison with the intake of rapidly absorbed sucrose in patients with T2DM [31].…”
Section: Discussionmentioning
confidence: 95%
“…Studies also showed that isomaltulose supplementation continuously over several months can improve glycaemic responses in both diabetic and non-diabetic, Caucasians and Japanese Asians [26,28]. Furthermore, van Can et al reported, less decline in fat oxidation during isomaltulose co-ingestion in overweight, impaired glucose tolerant subjects and improved glycaemia and insulin sensitivity [27].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of protein oxidation was assumed to be constant during the time in the WBC [59]. Although the study was performed in male subjects alone, previous studies have demonstrated a similar effect in mixed groups including men and women [26,28]. Serum insulin measurements could have significantly strengthened the study and further support the link between glycaemic response and fuel utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, low glycemic carbohydrates will lead to a longer postprandial energy supply by carbohydrates associated with a lower peak glycemic response. Ot is important to highlight that isomaltulose provides the same energy content (8 kJ or 4 kcal/g) provided by sucrose, however, in a balanced manner due to the slow release of glucose in the intestines increased of glycemia resulting from rapidly absorbed carbohydrates is avoided (Brunner et al, 2012;Holub et al, 2010) Ot has been demonstrated by several groups that a lower GO in meals is associated with a higher postprandial fat oxidation in healthy subjects (Wee et al, 2005). Considering obese subjects, the ingestion of isomaltulose with a lipid-rich meal also improved the profile of triglycerides and free fatty acids (FFA) in addition to the effects on postprandial glycemia (Suklaew et al, 2015).…”
Section: Influence Of Isomaltulose (Palatinose Tm ) On Postprandial Mmentioning
confidence: 99%